REGULATION, INCENTIVES AND GOVERNMENT POLICY: HOW DOES IT STIMULATE R&D ENGINEERS’ INNOVATIVE BEHAVIOURS IN MALAYSIAN BIOTECHNOLOGY SMEs? - Nurul Shamisza Sahrom; Cheng Ling Tan; Sofri Yahya (Asian Academy of Management Journal, 2016)
This study seeks to examine the relationship between regulation, incentives and government policy to R&D (research and development) engineers' innovative behaviour in Malaysia biotechnology SMEs. This research is empirical study where survey data was drawn from 218 R&D engineers in biotechnology SMEs in Malaysia. The data were analysed using SmartPLS which is Structural Equation Modelling (SEM) tool. The result unfolds that government policy is positively and significantly associated with innovative behaviour. Nevertheless, regulation was found significant to innovative behaviour but demonstrates negative magnitude. On the other hand, incentives was insignificant to innovative behaviour. This in turn suggests that government policy is critical to foster innovative behaviour whereby the regulation enforcement that indicates disequilibrium possess by higher compliance cost be a disincentive for the R&D engineers to act innovatively. Contradict to previous studies, the insignificant relationship between incentives and individual innovative behaviour, possibly influence by lack of coordination, monitoring and vetting system with regards to the incentives distribution.